Slit2/Robo4 Signaling: Potential Role of a VEGF-Antagonist Pathway to Regulate Luteal Permeability - Bekes, I.; Haunerdinger, V.; Sauter, R.; Holzheu, I.; Janni, W.; Wöckel, A.; Wulff, C. (Geburtshilfe und Frauenheilkunde, 2017)
Introduction The corpus luteum (CL) is dependent on luteal vascular permeability, which is controlled by human chorionic gonadotropin (hCG) via vascular endothelial growth factor (VEGF). In this study we investigated the role of a potential VEGF antagonist pathway – Slit2/Robo4 – and its influence on endothelial cell adhesion. Materials and Methods Luteinized granulosa cells (LGCs) were stimulated with hCG in the absence or presence of a VEGF inhibitor. The expression of VEGF and Slit2 were measured. Human umbilical vein endothelial cells (HUVECs) were stimulated with Slit2 or VEGF, and gene expressions of cadherin 5 (CDH5) and claudin 5 (CLDN5) were measured. Following Robo4 knockdown, CDH5, CLDN5 and endothelial permeability were measured. Results Stimulation of human LGCs with hCG significantly increased VEGF while Slit2 expression was significantly suppressed. Inhibition of VEGF action after hCG stimulation did not change Slit2 suppression. Slit2 knockdown did not affect VEGF expression. While VEGF stimulation of HUVECs significantly suppressed CDH5 and CLDN5 gene expression, stimulation of HUVECs with Slit2 resulted in a significant increase in CDH5 and CLDN5. Robo4 knockdown was done, leading to downregulation of CDH5 and CLDN5 which resulted in significantly increased permeability. Conclusions Our results indicate the existence of a VEGF-antagonist pathway in the CL that decreases vascular permeability. During the functional life of the CL the pathway is suppressed by hCG. It is possible that stimulation of this pathway could be used to treat ovarian hyperstimulation syndrome.
Keywords: VEGF; hCG; Slit2; luteal permeability; OHSS